“It's my body, I get to choose”: a mixed-method study on reactions towards Singapore's nutri-grade scheme and test of restoration postscripts - Chuah, Chong Koon (Nanyang Technological University, 2024)
In its “War on Diabetes,” Singaporean authorities introduced the Nutri-Grade labelling scheme, a front-of-pack nutrient summary label, aimed to help consumers make more informed and healthier choices regarding sugar-sweetened beverages (SSBs). This study investigates consumers’ reactions towards the Nutri-Grade label from a psychological perspective through a mixed-methods research design that involves photo-elicitation interviews and an online experiment conducted in two separate studies. Thematic analysis of the exploratory photo-elicitation interviews (N = 10) suggests that price is a key determinant of purchasing decisions and that the Nutri-Grade label can threaten consumers’ sense of freedom and elicit defensive reactions against the health message. The subsequent online experiment utilised a 2 (freedom threat; high, low) x 2 (restoration postscript; present, absent) study design to investigate the reactions towards anti-SSB health messages that included Nutri-Grade labels. Participants (N = 238) were randomly shown one of four health messages presented in a social media format. It was hypothesised that messages high in freedom threat would elicit reactance and defensive reactions against the messages, while restoration postscripts would mitigate reactance and increase persuasive outcomes. The manipulation of freedom threat had limited effects on participants’ reactance, anger and avoidance, while there were no significant effects on persuasive outcomes. Restoration postscripts were ineffective in reducing defensive reactions and improving persuasive outcomes. Discussion of both study’s findings and practical implications for public health campaigns are included in the following paper.